Effect of culture on oral health attitudes, behaviour and values among the dental students of two dental colleges in Chennai city- a cross sectional study - N Naveen; Nimisha Gopal; J Avinash; M A Adil Ahmed; D Prabu (Wolters Kluwer Medknow Publications, 2013)
Objective: To identify similarities and differences in oral health attitudes, behavior and values among 1 st year dental students studying in two dental colleges of Chennai city. Materials & Method: The study was carried out in two dental colleges of Chennai city among 120 first year dental students aged 18-19 years. They were grouped under different zones (north, East, South and West) and those who responded to the self-administered questionnaire were included in the study. An 18 item closed ended questionnaire primarily associated with oral health attitude, behaviour and tooth brushing was used. This questionnaire is a modified version of the Hiroshima University Dental Behavior Inventory (HU-DBI). Results: About 64% of the study subjects agreed that they were worried about visiting the dentist; 73.3% of the study subjects were concerned about the color of their teeth; the students from south and north were more concerned compared to the people from east. Significant differences (p<0.05) were seen among students of different zones regarding not worrying much about visiting the dentist, about bleeding gums while brushing, worrying about having a bad breath and the thought that it was impossible to prevent gum disease with tooth brushing alone. Conclusions: Statistically significant differences in the oral health attitude/behavior were recorded among 120 first year dental students from the two dental colleges in Chennai city yielding plausible results, using the HU-DBI. Oral health education needs to be provided in those areas where there are deficits in knowledge.